Proyecto de factibilidad para la implementación de una planta secadora de cacao en el recinto Federico Intriago del Cantón Valencia, Provincia de Los Ríos. - Quinto Morante, Nelly Maribel (2016)
The present project aims to conduct a feasibility study for the implementation of a cocoa dryer plant in the Federico Intriago Campus of Canton Valencia, province of Los Ríos. The applied methodology consisted in the use of analytical, deductive, inductive The types of applied research are bibliographical and of field the total universe is of 40 farmers of the Rectory Federico Intriago, of the canton Valencia, establishing that the collection of the data was done through the surveys to the farmers, conformed by 21 questions, the Which were distributed to analyze the market, technical and financial study. The results show that the supply is all the collection centers and commercial agricultural products that provide the drying service in the canton Buena Fe, since this is the place where the farmers of the enclosure Federico Intriago, in addition was determined according to the Technical study where the materials and specific prices for the design and elaboration of the cacao dryer machine were detailed, the same one that for being used for communal and non-industrial use will have a capacity of 10 to 15 qq of cacao. The capacity of the plant is analyzed in an engine consumption is 0.75 kw per hour and 2 to 3 kilos of gas per hour, so its performance is very efficient since drying per quintal would cost $ 2 dollars American people. The project is feasible since it is in line with its biggest problem, such as the drying of cocoa in the enclosure. In addition, according to the economic study based on the cash flow establishes a NPV (Net Present Value) of $ 3118.07 and an IRR (internal rate of return) of 50% also the data obtained in the investigation was found that the benefit ratio Cost of the same that is $ 1.14 (one dollar with fourteen cents), which means that for every dollar invested the company has $ 0.14 (fourteen cents), which determines that it is profitable.